Entrepreneurial processes in new company creation – an examination of private companies in the social service sector. Issue 3 (19th August 2014) - Gawel, Aleksandra; Toikko, Timo
Abstract : Purpose: This paper verifies the positive impact of legislative changes aimed at decontrolling the market on the entrepreneurial process of new companies' creation. The entrepreneurial process has been analysed in the context of innovation, risk and market opportunities, which represent the three main approaches to entrepreneurship theories. The analysis is focused on the social service sector in Finland. Design/methodology/approach: The study is based on an ex post facto research design. The data is based on official statistics and the data bank of legislation. The case of Finland is used as an example for explaining the determinants of new company creation. Findings: Legislative changes aimed at decontrolling the market seem to have a positive impact on the entrepreneurial process of new company creation. This influence is manifested in the form of market opportunities, risk bearing and the introduction of innovation. Of these three factors influencing the start-up process, the opportunities for market exploitation seem to have the greatest impact. In the Finnish social service sector, entrepreneurial opportunities are based on changes in the political structures that influence the market conditions. Entrepreneurs have also contributed to the opportunities by being active and innovative in filling any new gap in the market structures. Practical implications: These results might be useful in the debate on policies supporting entrepreneurship. The example of the Finnish social service sector indicates that political changes in market regulations are a very effective method of supporting the process of entrepreneurship. Originality/value: The paper is among the first to analyse both legislative changes and market changes affecting the entrepreneurial process, which indicates that the research is comprehensive. Second, legislative political actions to decontrol the market are a starting point in the discussion on the determinants of the entrepreneurial process. Thirdly, the contribution of legislative changes in terms of market opportunities, innovation and risk bearing as avenues of influence on the entrepreneurial process is analysed.